Supplementary enteral nutrition maintains remission in paediatric Crohn's disease. Issue 4 (April 1996) - Wilschanski, M; Sherman, P; Pencharz, P; Davis, L; Corey, M; Griffiths, A
Abstract : BACKGROUND–Liquid diets given enterally combined with "bowel rest' are efficacious in the treatment of active Crohn's disease, but rapid recrudescence of gastrointestinal symptoms after resumption of a normal diet is common. AIMS–This study examined whether continuation of enteral nutrition as a nocturnal supplement to an ad libitum daytime intake of a normal diet increased the length of remission of Crohn's disease in children. PATIENTS AND METHODS–Children and adolescents with active Crohn's disease treated successfully with exclusive enteral nutrition were classified retrospectively according to whether they continued supplementary enteral nutrition or not. Time to relapse and linear growth were compared between the two cohorts. RESULTS–Between January 1986 and December 1992, 65 patients aged 7-17 years (mean (SD) 13.6 (2.1) years) (36 males, 29 females) with Crohn's disease in exacerbation were treated for > or = four weeks by bowel rest and nasogastric tube feeding of an oligopeptide or amino acid based formula. At first follow up visit, remission (fall in Paediatric Crohn's Disease Activity Index, PCDAI to < or = 20) was achieved in 47 of 65 (72%) patients. Subsequently, 20 of these 47 (43%) relapsed by six months and 28 of 47 (60%) by 12 months. Patients who continued nasogastric supplementary feeding (n = 28) after resumption of an otherwise normal diet remained well longer than those who discontinued nocturnal supplements completely (n = 19) (p < 0.02). Furthermore, continued use of nasogastric supplements before completion of puberty was associated with improved linear growth. CONCLUSION–After successful treatment of active Crohn's disease by exclusive enteral nutrition, supplementary enteral nutrition without restriction of normal diet is associated with prolongation of remission and improved linear growth in children and adolescents.